THE PRACTICE OF BUYING AND SELLING GRAPHIC DESIGNS THROUGH A HIRING SYSTEM IN THE PERSPECTIVE OF AN ISTISNA' CONTRACT ON THE SRIBU.COM MARKETPLACE - Cut Azzahra Muly; Edi Darmawijaya (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The practice of buying and selling graphic designs through the Sribu.com marketplace via a hiring system is a phenomenon that facilitates collaboration between clients and designers efficiently and transparently. The problem in this research is how to practice buying and selling graphic designs on the Sribu.com marketplace through the hiring system and how to review the Istisna' contract. The results of this research indicate that from an Islamic legal perspective, this transaction can be interpreted as a form of istisna' contract, which involves determining specifications, prices and payments based on the work that has been done. Any discrepancy between the design and the client's brief may result in the cancellation of the transaction as a valid option, taking into account the principles of fairness in dispute resolution. This practice allows the application of Islamic values and business principles in accordance with religious law in the context of the graphic design trade.